EFFECTIVE TECHNOLOGIES FOR REMOTE MONITORING AND EVALUATION OF STUDENTS' EDUCATIONAL ACHIEVEMENTS TO MAINTAIN A CULTURE OF ACADEMIC HONESTY - Bektemesov, М.; Issabayeva, Д. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article deals with the issues of observing the culture of academic honesty in exams in distance learning. Based on their research, which was carried out for two years, the authors give recommendations on the organization of online exams, consider various types of control and the corresponding digital technologies that allow maintaining academic honesty. Identified possible violations during the online exam, analyzed the causes and proposed solutions. The types of exam that develop critical thinking and have zero tolerance for any violation of the academic integrity code are the open book written exam, design and practical exams, as well as testing and closed book written exam using a proctoring system. The principles that should become the norm for strengthening the culture of academic honesty are defined.